Restless Hearts: George Fox and Augustine of Hippo. Issue 2 (December 2017) - Birkel, Michael
Abstract : John Punshon once proposed that someone should undertake a comparison of early Quaker George Fox with ancient North African bishop Augustine of Hippo. Despite considerable differences between the two, a close look at turning points in their religious autobiographies shows common themes, particularly a Johannine sense of interiority and divine love. These turning points operated differently in their lives: for George Fox, it enabled him to embrace others whose unrighteousness had repulsed him, while, for Augustine, it enabled him to relax his terrified grip on those whom he loved.